Analisis penerapan good university governance pada pelayanan administrasi akademik dan kemahasiswaan menggunakan TOGAF ADM - Irma Rosalina; Yani Nurhadryani; Irman Hermadi (Jurnal Pendidikan Informatika dan Sains, 2022)
Good University Governance (GUG) is a college management concept that can improve the college quality in order to increase the public’s satisfaction and trust. The availability of academic, student data, as well inefficient business processes become issues in supporting quality improvement at Health Polytechnic Ministry of Health Palu. The study aimed to analyze the condition of GUG application in academic and student administration services at Health Polytechnic Ministry of Health Palu using The Open Group Architecture Framework Architecture Development Method (TOGAF ADM) stages. Identification of architectural principles and GUG principles are indicators of architectural goals to be achieved. The result indicated that there was a commitment related to the vision and mission of GUG, but the implementation of GUG principles could not be fulfilled. Inadequate use of application, report data which does not meet the needs of SPI and quality assurance, as well the elaboration of SOPs and authorities specifically are problems that make the objectives of transparency, accountability, quality assurance, and responsibility unfulfilled. The GUG principle determination into architectural principle is a strategic move in system development since GUG principle is an essential element in managing organizational needsKeywords: Good University Governance,TOGAF ADM,Academic Administrasi Service.